2016
DOI: 10.1080/02640414.2016.1150602
|View full text |Cite
|
Sign up to set email alerts
|

Scoring mode and age-related effects on youth soccer teams’ defensive performance during small-sided games

Abstract: This study aimed to examine the scoring mode (line goal, double goal or central goal) and age-related effects on the defensive performance of youth soccer players during 4v4 small-sided games (SSGs). Altogether, 16 male players from 2 age groups (U13, n = 8, mean age: 12.61 ± 0.65 years; U15, n = 8, 14.86 ± 0.47 years) were selected as participants. In six independent sessions, participants performed the three SSGs each during 10-min periods. Teams' defensive performance was analysed at every instant ball poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 28 publications
4
47
1
Order By: Relevance
“…The evaluation of the tactical-technical performance showed that with one small target, the occurrences of wrong passes, lost balls and conquered balls increased. These results corroborate those obtained in the study by Clemente et al 17 and Almeida et al 18 , who observed that with one small target, players organize better defensively, leading to failure in passing and greater ball possession conquest. The results of the present study can be explained by the players' behavior of focusing more on the central portion of the field to protect the small target 17,18 and in the closer proximity between teams 19 , thus reducing playing spaces.…”
Section: Discussionsupporting
confidence: 92%
“…The evaluation of the tactical-technical performance showed that with one small target, the occurrences of wrong passes, lost balls and conquered balls increased. These results corroborate those obtained in the study by Clemente et al 17 and Almeida et al 18 , who observed that with one small target, players organize better defensively, leading to failure in passing and greater ball possession conquest. The results of the present study can be explained by the players' behavior of focusing more on the central portion of the field to protect the small target 17,18 and in the closer proximity between teams 19 , thus reducing playing spaces.…”
Section: Discussionsupporting
confidence: 92%
“…To circumvent this problem increasingly multi-variate approaches are being used to retain contextual information (Fernandez-Navarro et al 2016; Kempe et al 2014). Almeida et al (2016) investigated the effect of different scoring modes on ball-recovery type and location, playing configuration and defensive state in youth players. The results showed that more ball recoveries were made when a central goal was used and that most recoveries were a result of set-play in the defensive third of the pitch.…”
Section: Analysis Of Soccer Tacticsmentioning
confidence: 99%
“…The results showed that more ball recoveries were made when a central goal was used and that most recoveries were a result of set-play in the defensive third of the pitch. Younger players also produced more elongated shapes in the playing direction whereas the older teams produced more flattened shapes with larger spread in the direction orthogonal to the playing direction (Almeida et al 2016). Tenga et al (2010a, b) investigated the effects of a ten different variables on score-box possession based on video data from 163 matches from the Norwegian men’s professional league in 2004.…”
Section: Analysis Of Soccer Tacticsmentioning
confidence: 99%
“…The SSG pitch was 30 m long by 20 m wide (playing area = 600 m 2 and individual interaction space = 75 m 2 per player). The relative pitch proportions were kept constant and had the same length-to-width ratio as an official soccer field (i.e., 1.46) [24].…”
Section: Small-sided Game (Ssg)mentioning
confidence: 99%